Un sistema de visualización para el Capital Intelectual (2019)
This article proposes a visualization and measurement system for the organizations’ Intellectual Capital. In the introduction, the article provides context about some concepts like intangible means for value generation, intellectual capital and knowledge management. Next, the article makes a comparative analysis of the two most successful methodologies for value visualization, currently in use in organizations. It analyses the pros and cons of each methodology and its similarities. Finally, the article proposes a model that takes advantage of the positive aspects and minimizes the negative aspects of the aforementioned methodologies. This model is easily applicable to all kinds of organizations —either profit or non-profit— and helps to identify and measure its intangible resources, making them visible to the stakeholders.